2021
DOI: 10.35194/jmtsi.v5i2.1427
|View full text |Cite
|
Sign up to set email alerts
|

Kelelahan Mata dan Keluhan MSDs Perkuliahan Daring Selama Pandemi COVID-19 pada Mahasiswa di Tiga Fakultas Universitas Sari Mulia (Program Studi Teknik Industri, D-IV Promosi Kesehatan dan Program Studi Manajemen)

Abstract: The spread of COVID-19 cases is very fast, affecting all sectors. One of these sectors is educational institutions. In order for the learning process to continue, an online  learning system was implemented. Online  learning causes an increase in sitting rather than standing, activity in front of a smartphone or laptop. The purpose of this study is to identify eye fatigue and MSDs complaints in students at three study programs, Industrial Engineering, DIV-Health Promotion and Management. The data was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…The research conducted by Tambun (2021) showed that musculoskeletal disorders were most common in the waist, with as many as 34 people (61.8%), 33 people (60%) in the upper neck, and 25 people (45.5%) lower neck. 20 The majority of participants had a low risk of musculoskeletal disorders. The risk of musculoskeletal disorders is related to corrective action.…”
Section: Methodsmentioning
confidence: 99%
“…The research conducted by Tambun (2021) showed that musculoskeletal disorders were most common in the waist, with as many as 34 people (61.8%), 33 people (60%) in the upper neck, and 25 people (45.5%) lower neck. 20 The majority of participants had a low risk of musculoskeletal disorders. The risk of musculoskeletal disorders is related to corrective action.…”
Section: Methodsmentioning
confidence: 99%
“…Pemakaian perangkat laptop maupun smartphone ketika proses belajar daring meningkatkan risiko mengalami keluhan MSDs (Tambun & Oktaviannoor, 2021) Selain alasan yang disebutkan diatas mahasiswa keperawatan mayoritas akan menjadi seorang perawat yang akan sering berhubungan langsung dengan klien, oleh karena itu penting untuk menerapkan posisi tubuh ergonomis sejak dini sehingga dapat bekerja dengan nyaman dan mengurangi kelelahan atau rasa sakit saat bekerja, karena seperti yang kita ketahui bahwa keselamatan pasien adalah kepentingan semua orang (Baringbing, 2020)…”
Section: Duniaunclassified
“…Aktivitas mahasiswa dengan durasi yang lama saat pembelajaran daring berlangsung >4 jam akan mempengaruhi posisi yang digunakan oleh responden. Durasi penggunaan laptop maupun smartphone dalam waktu ≥ 4 jam setiap hari pada posisi duduk yang membungkuk dan duduk di lantai sering kali berisiko mengalami keluhan kesehatan terkait penggunaan laptop maupun smartphone yaitu MSDs (Tambun & Oktaviannoor, 2021).…”
Section: Hubungan Durasi Penggunaan Laptop/smartphone Saat Pembelajar...unclassified
“…Based on previous research, students in three study programs of Sari Mulia University, almost all students, experience complaints of musculoskeletal disorder. The majority of MSDs complaints were experienced by students in the waist as many as 34 people (61.8%), in the upper neck as many as 33 people (60%) and on the lower neck as many as 25 people (45.5%) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia was one of the fastest countries infected with the COVID-19 virus with more than 100 new cases every day [3]. One of the steps taken by the government in preventing the transmission of the COVID-19 virus was by the enactment of physical distancing in all activities including one of them was in the field of education [4]. Educational institutions began to implement the process of distance learning (online) since the issuance of The Minister of Education Circular Letter No.…”
Section: Introductionmentioning
confidence: 99%